Quantitative assessment of signal quality and usability of EEG and EMG recordings with PEDOT:PSS-coated microneedle electrodes - Yamaguchi, Tomoya; Kurashina, Yuta; Nagahara, Eiji; Oshima, Sota; Kaneko, Naotsugu; Nakazawa, Kimitaka; Tanaka, Hideyuki; Yokoyama, Hikaru (Frontiers in Neuroscience, 2025)
IntroductionBioelectrical signals are vital indicators of physiological function, psychological status, and clinical conditions. However, traditional wet electrodes using conductive gel are time-consuming, labor-intensive, and degrade over time due to gel drying. Recently, microneedle (MN) electrodes coated with poly(3,4-ethylene dioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) have been developed for high-quality signal acquisition. Although low electrode–skin impedance has been demonstrated on hairless regions, their use in electroencephalography (EEG) recordings on hairy scalp areas and quantitative comparisons with conventional electrodes in both EEG and electromyography (EMG) remain limited.MethodsWe fabricated two MN electrode types of different lengths—one for EMG on hairless skin and one for EEG on the hairy scalp—and compared them with conventional wet and dry electrodes. EMG was recorded during a force-matching task; EEG was assessed via somatosensory evoked potentials. We also evaluated setup/cleanup time, comfort, and pain during EEG measurement.ResultsFor EMG, MN electrodes achieved significantly higher signal-to-noise ratios than conventional electrodes. For EEG, they outperformed dry electrodes and matched wet electrodes in signal quality—without using conductive gel. Although additional time was required to part hair, cleanup was faster due to the absence of gel. Pain was comparable to dry electrodes.DiscussionPEDOT:PSS-coated MN electrodes provided superior EMG signal quality and high-quality EEG signals comparable to wet electrodes even without gel. These findings suggest that PEDOT:PSS-coated MN electrodes offer a compelling balance of signal quality and user convenience, making them especially advantageous for real-world and clinical applications where time efficiency, minimal discomfort, and gel-free operation are critical.